Measurement of Adenosine Deaminase in Ascitic Fluid Contributed to the Diagnosis in a Case of Tuberculous Peritonitis - Kishimoto, Kenichi (Case Rep Gastroenterol, 2019)
A diagnosis of tuberculous peritonitis (TBP) is difficult because of nonspecific manifestation and limited effectiveness of conventional diagnostic tools. Recently, the usability of measurement of ascitic adenosine deaminase (ADA) was shown. We report here a case of TBP in which measurement of ascitic ADA contributed to the diagnosis. A 93-year-old male developed a large amount of ascites. Analyses of the ascitic fluid revealed exudation, though antibiotics treatment was ineffective. Using paracentesis, the ADA level in the ascites was measured and shown to be high. Under suspicion of TBP, an exploratory laparoscopy was performed and a definitive diagnosis of TBP was made.